2022
DOI: 10.1002/cam4.4814
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐associated macrophages regulate the function of cytotoxic T lymphocyte through PD‐1/PD‐L1 pathway in multiple myeloma

Abstract: Background: Tumor-associated macrophages (TAMs) are originated from circulating mononuclear cells in peripheral blood. They result from the recruitment of tumor cells and are a vital constituent of the tumor microenvironment. TAMs may be involved in the immunological escape of vicious clonal plasma cells (PC) in the bone marrow (BM) of sufferers with myeloma.Methods: From March 2020 to January 2021, 28 healthy controls (HC) and 86 multiple myeloma (MM) (53 newly diagnosed MM [NDMM] and 33 remissions) patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In vivo, the administration of the anti CSF-1 receptor antibody CS7 significantly reduced the MM tumor burden, while the in vitro administration of low-dose CS7 could contribute to TAM polarization towards an M1 subtype [110]. M1 TAM showed an improved antigen-presenting capacity and the ability to enhance a cytotoxic CD4 + T cell response, further supporting the hypothesis that M2 TAM, conversely, play a relevant role in the decreased T cell activation and resulting immunosuppression reported in MM, ultimately leading to disease progression [110].…”
Section: Mouse Model Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo, the administration of the anti CSF-1 receptor antibody CS7 significantly reduced the MM tumor burden, while the in vitro administration of low-dose CS7 could contribute to TAM polarization towards an M1 subtype [110]. M1 TAM showed an improved antigen-presenting capacity and the ability to enhance a cytotoxic CD4 + T cell response, further supporting the hypothesis that M2 TAM, conversely, play a relevant role in the decreased T cell activation and resulting immunosuppression reported in MM, ultimately leading to disease progression [110].…”
Section: Mouse Model Studiesmentioning
confidence: 99%
“…In vitro, an anti-CD47 antibody significantly improved the ability of macrophage to engulf MM cells [113,114]. In addition, TAM could drive immune tolerance, due to co-culture with TAM could increase programmed death receptor 1(PD1) expression on CD8 + T cells and programmed death receptor ligand 1 (PD-L1) expression on MM cells [102,110].…”
Section: Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-32γ can promote drug resistance in MM through macrophages and modify macrophages towards an M2 phenotype [316]. Increased TAMs in MM patients can stop the functions of cytotoxic T lymphocytes (through the PD-1/PD-L1 pathway) and contribute to the evasion of the immune system by myeloma cells [317]. Exosomes, derived from MM containing IL-32γ, can increase the expression of PD-L1 by macrophages and lead to immune evasion.…”
Section: Macrophage Role In Multiple Myelomamentioning
confidence: 99%
“…Recent research suggests that macrophages contribute to the growth, viability, and drug resistance of myeloma cells through both direct and indirect mechanisms 17,18 . Moreover, studies have demonstrated an expansion of TAMs in patients with MM and their involvement in suppressing the anti‐tumor activity of cytotoxic T lymphocytes (CTLs) via the PD‐1/PD‐L1 signaling pathway, thus aiding in the immune evasion of myeloma cells 19 . Despite these findings, the precise mechanisms underlying the immunosuppressive polarization of TAMs in MM remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%